1977
DOI: 10.1021/i360062a006
|View full text |Cite
|
Sign up to set email alerts
|

Methanation Sutdies on Nickel-Aluminum Flame-Sprayed Catalysts

Abstract: Methanation catalysts were prepared by flame-spraying aluminum onto a nickel surface followed by heating to form a Raney-type alloy and then activating with a caustic leach. Different alloying temperatures from 400 to 950 °C were employed. A maximum in methanation activity occurred for a sample alloyed at 725 °C. Little alloying occurred for catalysts preheated at 400 °C whether for 1 h or for 910 h and low activities were obtained. This indicates that active catalysts were not formed by a slow diffusion proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

1979
1979
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 2 publications
2
5
0
Order By: Relevance
“…The alloy phases formed at 700 and 800 °C were composed of NiAl3 with a very little Ni2Al3 and Ni2Al3 with a little NiAl3, respectively. This is the same as those reported in the previous papers (Nakabayashi et al, 1969) and is consistent with the detailed investigation by Baird and Steffgen (1977). Analysis of the pattern of nickel aluminide-coated iron plate (method B) indicated that this Raney nickel alloy did not contain NiAl3 or Ni2Al3 but did contain NiAl and Ni3Al.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…The alloy phases formed at 700 and 800 °C were composed of NiAl3 with a very little Ni2Al3 and Ni2Al3 with a little NiAl3, respectively. This is the same as those reported in the previous papers (Nakabayashi et al, 1969) and is consistent with the detailed investigation by Baird and Steffgen (1977). Analysis of the pattern of nickel aluminide-coated iron plate (method B) indicated that this Raney nickel alloy did not contain NiAl3 or Ni2Al3 but did contain NiAl and Ni3Al.…”
Section: Resultssupporting
confidence: 91%
“…The active nickel catalyst is prepared by leaching the aluminum in an aluminum-nickel alloy. Although a similar technique has been used by others (Larson, 1974; Baird and Steffgen, 1977) to prepare hydrogenation catalyst, the hydrogenation activity of the alloy containing only NiAl and Ni3Al has not bee reported.…”
Section: Introductionmentioning
confidence: 99%
“…The surface areas of plasma-sprayed catalysts using nitrogen were found to be too small to be meaningful. Similar problems were encountered by Baird and Steffgen (1977) while measuring the BET areas for nickel-aluminum flame-sprayed catalysts. Therefore, krypton gas was used for surface area measurements.…”
Section: Resultssupporting
confidence: 75%
“…Similar trend has been reported by Feimer et al, 1981and Zarochak et al, 1982, but according to Dry, 1976, the influence of temperature is not always clearcut and its relative effect on selectivity seems to depend on the type of catalyst, temperature range being considered and on the process conditions. As reported in the literature, carbon dioxide is formed as a result of water-gas shift reaction (Dry et al, 1972;Baird et al, 1977;Feimer et al, 1981;Rofer-DePoorter, 1981;Arcuri, 1982). Thus, higher temperature favours the formation of lower molecular weight compounds.…”
Section: Effect Of Temperature and Exposure Velocitymentioning
confidence: 74%
“…Table 3 lists the weight percentages of hydrocarbons, water and COz obtained at different exposure velocities at 260"C, 6.89 X lo5 Pa and Hz/CO feed ratio of 2. As reported in the literature, carbon dioxide is formed as a result of water-gas shift reaction (Dry et al, 1972;Baird et al, 1977;Feimer et al, 1981;Rofer-DePoorter, 1981;Arcuri, 1982). A slight decrease in the extent of water gas shift reaction was observed at higher exposure velocities.…”
Section: Effect Of Temperature and Exposure Velocitymentioning
confidence: 74%